The Influence of Market Orientation, Innovation, and Competitive Advantage as Intervening Variable on Marketing Performance of Culinary MSMES in Purwokerto - Afif, Nur Choirul; Faradina, Hanifah (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2023)
This research aims to find out whether market orientation and innovation with a competitive advantage as mediation have a positive influence towards the marketing performance of Culinary MSMEs in Purwokerto. In this research, a questionnaire was used to perform a quantitative type of data analysis on 100 respondents from four sub-district in Purwokerto, and this research used a purposive sampling method. The data analysis used in this research is SEM-PLS. By using these variables, it concludes the output data of this research that: (1) there is positive and significant influence from market orientation and innovation towards competitive advantage, (2) there is positive and significant influence from market orientation, innovation, and competitive advantage towards marketing performance, (3) competitive advantage mediates the influence of market orientation and innovation towards marketing performance.